Test Activity Extract Ethanol of Durian (Durio zibethinus Murr.) on Bacteria Propionibacterium acnes and Staphylococcus aureus - SAFITRI, ANDI TENDRIANI (Jurnal Farmasi Udayana; Vol. 9, No. 2, Tahun 2020DO - 10.24843/JFU.2020.v09.i02.p01, 2020)
Durian peel (Durio zibethinus Murr) is a plant that can be used as a treatment. Durian skin contains secondary metabolites, namely flavonoids which have antibacterial activity. The bacteria that cause acne are Propionibacterium acnes and Staphylococcus aureus. The extract was obtained by maceration using 70% ethanol solvent. The ethanol extract of durian peel obtained was made in 3 series of concentrations of 10%, 15% and 25% then tested on propionibacterium acnes and staphylococcus aureus bacteria. The MIC value of Propionibacterium acnes bacteria obtained was 10% with an area of ??inhibition zone formed of 7.5 mm ± 0.4 mm. 15% with an area of ??inhibition zone formed of 7.7 mm ± 0.3 mm. 25% with an area of ??inhibition zone formed of 8.4 mm ± 0.2 mm while the MIC value of the Staphylococcus aureus bacteria obtained was 10% with an area of ??inhibition zone formed of 8.11 mm ± 0.4 mm. 15% with an area of ??inhibition zone formed of 8.11 mm ± 0.3 mm. 25% with an area of ??inhibition zone formed of 8.8 mm ± 0.5 mm. based on the results of ethanol extract durian skin has activity against Propionibacterium acnes and Staphylococcus aureus. Keywords: Durio zibethinus Murr, Acne, Propionibacterium acnes, Staphylococcus aureus